The world according to physics - Al-Khalili, Jim, 1962- (Princeton University Press, 2020)
"This book frames the nature and importance of modern physics in an accessible, compelling, succinct way, showing lay readers that physics is crucial to our modern understanding of the world--and indeed the world as we currently know and experience it. Through the narrative, the book naturally describes essential facets of what physics is and why it has become such a (some might say, the) fundamental science. In addition, the reader will gain a sense of the grand scope and sweep of science and the collective, self-correcting nature of how science is done. For some, the book may serve as an invitation to physics. To others, it may serve to clarify the role of physics and describe a shared, global, centuries-long quest for fundamental knowledge"--